SURFACE PROTECTION: CONSERVING THE RELATIONSHIP BETWEEN ARTIST AND MATERIAL IN ISFAHAN AND TCHOGHA ZANBIL, IRAN - Vahidzadeh, Reza; Pedram, Behnam; Reza Owlia, Mohammad (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
Surface protection of Iranian earthen architecture has been continuously accomplished with a variety of decorative covering materials based on traditional symbolism and vernacular aesthetic, which relect two general principles: high lexibility and sacriicial decorative material for protecting the inner meaning (the spirit) of the architectural space. This cultural phenomenon enjoys strong theoretical foundations, as well as technical skills that are transferred by generations of traditional artists through speciic training patterns in the process of repair and maintenance of historical buildings. Considering this issue is essential to achieve a holistic approach towards the tangible and intangible dimensions of historic earthen architecture. This paper presents the experiences of conservators and local craftsmen in evaluating the state of transferring this intangible heritage during the conservation programs in historic (Tchogha Zanbil) and traditional (Isfahan) environments. A four-year program of evaluation and cooperative interviews shows that the conservation workshops have provided a supportive ield for rethinking vernacular knowledge of construction. However, in the absence of a common language among younger and older generations of local artists and conservators for exchanging the ideas about cultural values, their cooperation may be reduced into a few technical details. In order to present the intangible values of traditional maintenance to the conservators, promoting these traditions among the younger generation of craftsmen, and recognizing the craftsmen not as technicians but as creative agents in the conservation system, practical measures were proposed. These measures include participation of local artists in developing conservationmanagement plans and publications, dedicating virtual spaces for introducing local repair systems to the public, and promotion of creative and critical approaches towards conservation technology through the joint participation of local artists and conservators in training workshops.